Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/machines11080796
|View full text |Cite
|
Sign up to set email alerts
|

Building a Digital Twin Powered Intelligent Predictive Maintenance System for Industrial AC Machines

Abstract: Predictive maintenance is a system’s competency in distinguishing future scenarios where the machine is likely to fail and schedule repairs just prior to this happening. A heuristic technology to enable efficient predictive maintenance is digital twin technology. The development of a twin system between real-time machinery and the virtual world is made possible by digital twin technology, which is ideal for predictive maintenance. Induction motors, which are the core of industrial machinery, are sparsely repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Notably, this study indicated that eight studies applied ML techniques for PdM through data-driven modelling across various sectors such as aeroplane maintenance, automobile brake pads, and induction motors ( Altun & Tavli, 2019 ; Avornu et al, 2022 ; Heim et al, 2020 ; Mubarak et al, 2022 ; Rajesh et al, 2019 ; Rossini et al, 2020 ; Siddiqui, Kahandawa & Hewawasam, 2023 ; Singh et al, 2023 ). Additionally, performance prediction studies have demonstrated the potential of ML as a useful technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, this study indicated that eight studies applied ML techniques for PdM through data-driven modelling across various sectors such as aeroplane maintenance, automobile brake pads, and induction motors ( Altun & Tavli, 2019 ; Avornu et al, 2022 ; Heim et al, 2020 ; Mubarak et al, 2022 ; Rajesh et al, 2019 ; Rossini et al, 2020 ; Siddiqui, Kahandawa & Hewawasam, 2023 ; Singh et al, 2023 ). Additionally, performance prediction studies have demonstrated the potential of ML as a useful technique.…”
Section: Resultsmentioning
confidence: 99%
“…8 , the percentage of PM in previous studies was 41%. The 14 studies involved in PM are Aivaliotis et al (2023) , Aivaliotis, Georgoulias & Chryssolouris (2019) , Aivaliotis et al (2019) , Altun & Tavli (2019) , Avornu et al (2022) , Centomo, Dall’Ora & Fummi (2020) , Heim et al (2020) , Liu et al (2019) , Mubarak et al (2022) , Rajesh et al (2019) , Rossini et al (2020) , Siddiqui, Kahandawa & Hewawasam (2023) , Singh et al (2023) and Yakhni et al (2022) . PMs also have drawbacks, such as being time-consuming and expensive to destroy and restore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation